Anabaena sp. DyP‐type peroxidase is a tetramer consisting of two asymmetric dimers. Issue 1 (16th November 2015) - Yoshida, Toru; Ogola, Henry Joseph Oduor; Amano, Yoshimi; Hisabori, Toru; Ashida, Hiroyuki; Sawa, Yoshihiro; Tsuge, Hideaki; Sugano, Yasushi
ABSTRACT: DyP‐type peroxidases are a newly discovered family of heme peroxidases distributed from prokaryotes to eukaryotes. Recently, using a structure‐based sequence alignment, we proposed the new classes, P, I and V, as substitutes for classes A, B, C, and D [Arch Biochem Biophys 2015;574:49–55]. Although many class V enzymes from eukaryotes have been characterized, only two from prokaryotes have been reported. Here, we show the crystal structure of one of these two enzymes, Anabaena sp. DyP‐type peroxidase (AnaPX). AnaPX is tetramer formed from Cys224‐Cys224 disulfide‐linked dimers. The tetramer of wild‐type AnaPX was stable at all salt concentrations tested. In contrast, the C224A mutant showed salt concentration‐dependent oligomeric states: in 600 m M NaCl, it maintained a tetrameric structure, whereas in the absence of salt, it dissociated into monomers, leading to a reduction in thermostability. Although the tetramer exhibits non‐crystallographic, 2‐fold symmetry in the asymmetric unit, two subunits forming the Cys224‐Cys224 disulfide‐linked dimer are related by 165° rotation. This asymmetry creates an opening to cavities facing the inside of the tetramer, providing a pathway for hydrogen peroxide access. Finally, a phylogenetic analysis using structure‐based sequence alignments showed that class V enzymes from prokaryotes, including AnaPX, are phylogenetically closely related to class V enzymes from eukaryotes. Proteins 2016; 84:31–42. © 2015 Wiley Periodicals, Inc.